Financial Analysis of the Use of Chrome Waste Material in the Construction of Plant mix Base Layer - Seferoğlu, Mehmet Tevfik; Acı, Elif Nur (Fırat University, 2025)
The purpose of this research is to determine the financial benefits of using certain proportions of chrome (Cr) waste material, which is a result of ore production activities in Kop Mountain (Bayburt) chrome mine site and has no economic value, for a plant mix base (PMB) layer to be designed in accordance with the Türkiye Highway Technical Specification standards. Cost analyses of waste mixture ratios were performed, and an economic evaluation was made depending on the distance to the chrome waste supply point, including the PMB layer construction costs of a highway. As a result of the study, it was determined that the use of the mixture with 100% Cr content in PMB type-1 layers is possible and provides a financial gain of over 18% even for the longest distance compared to the layer designed with 100% natural aggregate (NA). It was concluded that Cr waste materials can be an alternative to Da for PMB type-1 layers and that they will provide satisfactory economic benefits in addition to environmental benefits.

Bu araştırmanın amacı, Karayolu Teknik Şartnamesi (KTŞ) standartlarına uygun tasarlanacak olan bir plentmiks temel (PMT) tabakası için Kop Dağı (Bayburt) krom maden sahasında cevher üretim faaliyetleri sonucu ortaya çıkan ve ekonomik değeri bulunmayan atıl durumdaki krom (Cr) pasa malzemesinin belirli oranlarda kullanımının sağlayacağı mali faydaların belirlenmesidir. Pasa karışım oranlarının maliyet analizleri yapılarak bir karayolunun PMT tabakası yapım maliyetleri de dahil olmak üzere krom pasasının temin noktasına olan mesafeye bağlı ekonomiklik değerlendirmesi yapılmıştır. Çalışma neticesinde %100 Cr içerikli karışımının PMT tip-1 tabakalarında kullanımının mümkün olduğu ve %100 doğal agrega (Da) ile tasarlanan tabakaya kıyasla en uzak mesafe için bile %18’in üzerinde mali kazanç sağladığı belirlenmiştir. Cr pasa malzemelerinin, PMT tip-1 tabakaları için Da yerine alternatif olabileceği ve çevresel faydaların yanısıra tatmin edici ölçüde ekonomik fayda da sağlayacağı sonucuna varılmıştır.
Plentmiks Temel Tabakası Yapımında Krom Pasa Malzemesi Kullanımı ve Ekonomik Analizi
Keywords: Transportation Engineering; Ulaştırma Mühendisliği